Employee Engagement dan Kinerja Perawat dalam Pencegahan Penularan Infeksi Virus COVID-19 - Ardin S Hentu; Saka Adhijaya Pendit (Jurnal Keperawatan Silampari, 2022)
This study aims to analyze whether there is a relationship between the application of Employee Engagement and the performance of nurses in preventing the transmission of Covid-19 virus infection, especially at Madani Hospital and Update Hospital Palu. This research method is quantitative research with a cross-sectional approach. The results showed that after the Chi-Square test with an error rate of 0.05, the P-Value = 0.000 statistical test results were obtained. In conclusion, there is a significant relationship between Employee Engagement and the performance of nurses in handling the spread of the Covid-19 virus. Keywords: Covid-19, Employee Engagement, Nurse Performance